Técnicas didácticas para mejorar la pronunciación del lenguaje en los niños de 5 años del nivel inicial de la l.E. Nº 298, distrito de Rioja - 2010 - Pérez Meza, Chelita Sunny (2011)
Present study has as objective to determine him l. E. I influences her of the technical didactics in the pronunciation of the language, in the 5 years children of her initial level. 298, Rioja's district. Study was structured taking as person giving a reference the existent- investigations background and Roger Brown's, Chomsky's, Bruner's, Vygotsky's and Estern's models. Taking as person giving a reference mentioned theories, fact-finding hypothesis was formulated: the technical didacticses's application improves significantly the pronunciation of the language in the communication area in the 5 - years children of her initial level l.E.I. 298. Sector Democracia - Rioja. The sign once was considered in order to the study was elected intervening the aleatory sampling simple, shaped for the 18 five - years boys and girls of her lnstitution Educativa N. it happened To the sign that they administered a first observation to determine the pronunciation level of the language before the experience. Next he was applied technical didacticses and successively applied it observation to determine the influence of the technical didacticses in the language's pronunciation seconds her. Once obtenidos the data he carne from to the analysis and respective interpretation the same things, getting confirmed they improved than the technical didacticses's application the pronunciation of the language, in the 5 years children of her initial level l. E. l. 298, Rioja's district.